Preferensi Konsumen terhadap Atribut Eksternal Beras Organik di Yogyakarta - Sania S. Octovanny Mahmud; Rachmat Pambudy; Netti Tinaprilla (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2024)
Yogyakarta Special Region Province is the region displayed by Google Trends for the highest searches for the word “organic rice” on the period June 2019 – May 2020. Consumer preferences are very important because they are closely related to increased consumption. Organic rice business actors need to know the purchasing decision process and consumer preferences scientifically in determining the right marketing strategy and can be competitive in the market. Therefore, the purpose of this study is to analyze the purchasing decision process and the combination of organic rice attributes that are in accordance with the preferences of organic rice consumers in Yogyakarta. This study has a sample size of 111 respondents domiciled in Yogyakarta. The sampling method was carried out by purposive sampling. The analysis methods used are descriptive analysis and conjoint analysis. The results of the study show that the combination of organic rice attributes that are in accordance with the preferences of organic rice consumers in Yogyakarta is organic rice with an organic certificate with a utility value of 0.298; white with a utility value of 0.615; soft claims with a utility value of 0.157; and vacuum-packed with a utility value of 0.167. Future suggestions are given to farmers, agricultural extension workers, and organic rice entrepreneurs to have integrity with each other to develop the organic rice business.